2008
DOI: 10.1111/j.1365-2788.2008.01065.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of maladaptive behaviour in young children with Autistic Disorder

Abstract: Findings highlight the need to include behavioural management strategies aimed at increasing social engagement, sustained attention and decreasing aggressive behaviour in comprehensive intervention programmes for young children with AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
180
5
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(211 citation statements)
references
References 42 publications
19
180
5
7
Order By: Relevance
“…1 This may be particularly problematic for young children (< age 5 years) with a diagnosis of autism, 34% of whom experience clinically significant maladaptive behaviors. 2 Recent literature suggests that low nonverbal IQ and impaired communication abilities in young children place them at a higher risk for maladaptive behaviors. 3 Although these maladaptive behaviors are not a core feature of autism, they can significantly interfere with a child's educational and developmental progress.…”
Section: Introductionmentioning
confidence: 99%
“…1 This may be particularly problematic for young children (< age 5 years) with a diagnosis of autism, 34% of whom experience clinically significant maladaptive behaviors. 2 Recent literature suggests that low nonverbal IQ and impaired communication abilities in young children place them at a higher risk for maladaptive behaviors. 3 Although these maladaptive behaviors are not a core feature of autism, they can significantly interfere with a child's educational and developmental progress.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have described trends related to frequency and severity changes (or intensity) in crisis behaviors for decades but what is reported appears not to be focused on searching for general rules or definite laws in an analytical way. Moreover, some results seem controversial [9][10][11][12][13][14]. It is noteworthy that crisis behavior has been described as the "tip of the iceberg" [15] suggesting that its underlying reason seems to be the result of a complex interplay of many different variables, almost impossible to identify in a clear way [7,16].…”
Section: Complexitymentioning
confidence: 99%
“…Studies have also tackled the prevalence of CBs among children with ID (e.g., Dekker et al 2002;Farmer and Aman 2011;Ruddick et al 2015). These studies have usually focused on a specific behavior, such as aggressive behavior (e.g., Pavlovic et al 2013) or self-injurious behavior (e.g., Symons et al 2003), or on a specific disability or disorder, such as autism spectrum disorder (ASD; e.g., Hartley et al 2008;Jang et al 2011). Overall, research has found that the prevalence rates of aggressive and self-injurious behaviors range, respectively, from 10.8 and 5.3% (children with ID; Ruddick et al 2015) to 85 and 80% (participants with fragile X syndrome; Newman et al 2015).…”
Section: Introductionmentioning
confidence: 99%